2021
DOI: 10.3390/jcm10102108
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Liquid Biopsy in Gastric Cancer

Abstract: (1) Background: Liquid biopsy (LB) is a novel diagnostic method with the potential of revolutionizing the prevention, diagnosis, and treatment of several solid tumors. The present paper aims to summarize the current knowledge and explore future possibilities of LB in the management of metastatic gastric cancer. (2) Methods: This narrative review examined the most recent literature on the use of LB-based techniques in metastatic gastric cancer and the current LB-related clinical trial landscape. (3) Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 117 publications
(144 reference statements)
1
17
0
Order By: Relevance
“…The non-invasive concepts rendered liquid biopsy unparalleled charm and advantages. Its application value lies in tumor occurrence and progression monitoring, systemic therapy response prediction and early detection of metastatic disease (53). As a kind of circRNAs detectable in plasma, Hsa_circ_0000745 was involved in development processes of (GC) and may serve as promising diagnostic marker for GC in combination with CEA (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-invasive concepts rendered liquid biopsy unparalleled charm and advantages. Its application value lies in tumor occurrence and progression monitoring, systemic therapy response prediction and early detection of metastatic disease (53). As a kind of circRNAs detectable in plasma, Hsa_circ_0000745 was involved in development processes of (GC) and may serve as promising diagnostic marker for GC in combination with CEA (54).…”
Section: Discussionmentioning
confidence: 99%
“…Published results showed that ctDNA levels in GI tumors were significantly higher compared to non-GI tumors. Interestingly, one-third of the alterations detected in tumors were detected only in ctDNA, not in the tissue sample (53,56). In a prospective trial that has enrolled 93 patients with resectable gastric cancer, patients with CTCs ≥ 5/7.5 mL detected in postoperative blood samples had significantly inferior disease-free survival (DFS) and overall survival (OS) than those with a smaller number of CTCs (57).…”
Section: Discussionmentioning
confidence: 99%
“…[ 67 ]). As an illustration, we review several key roles for cancer-related exosomes below; more comprehensive reviews of exosomes in various neoplastic diseases have been published recently [ [68] , [69] , [70] , [71] , [72] ].…”
Section: Exosomes As Diagnostic Toolsmentioning
confidence: 99%
“…This article provides an overview of current and future applications of plasma ctDNA-based assays in select advanced solid malignancies, including recent guidelines and recommendations. The review focuses on breast, prostate, ovarian, lung, and colorectal malignancies, but the application of plasma-based testing extends to several other solid tumors and has been highlighted in recent comprehensive reviews [ 14 , 15 , 16 , 17 , 18 ]. In addition, the results of recent trials demonstrating the clinical utility of plasma ctDNA assays are interpreted in the context of current clinical practice and the evolving treatment landscape for solid tumors.…”
Section: Introductionmentioning
confidence: 99%